Implementation of Teaching Modules at State Elementary School 6 Langkai School - Alpida, Alpida; Puput, Puput; Lien Meilam; Melina Tricia; Matius Timan Herdi Ginting (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Basic education plays a crucial role in shaping the character of students, emphasizing both academic growth and the internalization of moral and spiritual values. State Elementary School (SDN) 6 Langkai School in Palangka Raya applies a non-differentiated teaching module that focuses on delivering uniform material to all students, promoting an inclusive and simple learning environment. Despite challenges such as limited facilities, a less comfortable learning environment, and students' varying levels of understanding, the module aims to foster social and moral values in alignment with the local context. This study examines the implementation of the module, the challenges faced by teachers, and its impact on students' learning outcomes. A qualitative approach, including in-depth interviews, direct observation, and document analysis, was used to gather data. The results emphasize the importance of improving teacher competencies, enhancing school facilities, and adopting active learning methods to overcome existing challenges and ensure the module's effectiveness in delivering quality education.